Normal values of key pinch strength in a healthy nigerian population (2015)
Background: With the severity of machine hand injuries in our environment, the need to determine the normal values for key pinch strength with which to compare restorative surgeries was justified. Methods: A cross sectional survey of participants who had no previous hand injuries limiting hand function. Data obtained included age, gender, body mass index, hand dominance and hand span. The Baseline Hydraulic Pinch Gauge was used to obtain key pinch strength. The influence of the above variables on measured pinch strength was analyzed using independent sample t-tests and Pearson’s correlation. Results: Of the 242 recruited participants, age range between 20 and 80 years, 163(67.4%) were male and 79 (32.6%) were female. Males had higher pinch strength (right-8.3 ±2.7kg, left-7.6±2.5kg) than females (right-6.3±1.5kg, left- 5.8±1.5kg). Pinch strength varied with age peaking in the fifth decade in males and females. Interestingly, the left handed dominant female had higher right pinch strength than her right handed counterpart (p<0.009). Height, and hand span correlated with pinch strength in females. Conclusion: Normal values for key pinch strength in this Nigerian population are lower than that of Caucasians.